Blood Flow Restriction Resistance Exercise Improves Muscle Strength and Hemodynamics, but Not Vascular Function in Coronary Artery Disease Patients: A Pilot Randomized Controlled Trial - Kambič, Tim; Novaković, Marko; Tomažin, Katja; Strojnik, Vojko; Jug, Borut (Frontiers in Physiology, 2019)
Resistance training may be associated with unfavourable cardiovascular responses. In healthy adults, blood flow-restricted (BFR) resistance training improves muscle strength and hypertrophy improvements at lower loads with minimal systemic cardiovascular adverse responses. The aim of this study was to assess the safety and efficacy of BFR resistance training in patients with coronary artery disease (CAD) compared to usual care. Patients with stable CAD were randomized to either 8 weeks of supervised biweekly BFR resistance training (30-40 % 1RM unilateral knee extension) or usual exercise routine. At baseline and after 8 weeks, patients underwent 1-RM knee extension tests, ultrasonographic appraisal of vastus lateralis muscle diameter and of systemic (brachial artery) flow-mediated dilation, and determination of markers of inflammation (CD40 ligand and tumor necrosis factor alfa), and fasting glucose and insulin levels for homeostatic model assessment (HOMA). A total of 24 patients (12 per group, mean age 60±8 years, 4 [17%] women) were included. No training-related adverse events were recorded. BFR-resistance training significantly increased muscle strength (1-RM, +8.96 kg, p<0.001 in BFR-RT group vs. +2.88 kg, p=0.004 in the control group), and decreased systolic blood pressure (-6.77 mmHg; p=0.030), whereas vastus lateralis diameter (+0.09 cm, p=0.096), brachial artery flow-mediated vasodilation (+1.55 %; p=0.079) and insulin sensitivity (HOMA IR change of 1.15, p=0.079) did not improve significantly. Blood flow restricted resistance training is safe and associated with significant improvements in muscle strength, and may therefore provide a feasible exercise option to improve skeletal muscle functioning in patients with CAD.